Effects of metformin and Exenatide on insulin resistance and AMPKα-SIRT1 molecular pathway in PCOS rats - Tao, Xin (J Ovarian Res, 2019)
AIMS: This study was designed to evaluate the protective effects of AMPKα and SIRT1 on insulin resistance in PCOS rats, and to illuminate the underlying mechanisms. METHODS: An in vitro PCOS model was established by DHEA (6 mg/(100 g•d)), and the rats were randomly divided into the metformin group (MF group, n = 11), the exenatide group (EX group, n = 11), the PCOS group (n = 10), and the normal control group (NC group, n = 10). The MF group was administered MF 300 mg/(kg•d) daily. The EX group was subcutaneously injected EX 10μg/(kg•d) daily. After 4 weeks of continuous administration, fasting blood glucose and serum androgen, luteinizing hormone and other biochemical indicators were measured. Western and Real-time PCR were used to determine the expression of AMPKα and SIRT1 in the ovaries of each group. RESULTS: After 4 weeks of drug intervention, compared with untreated PCOS group, EX group and MF group had visibly decreased body weight (222.64 ± 16.57, 218.63 ± 13.18 vs 238.30 ± 12.26 g, P = 0.026), fasting blood glucose (7.71 ± 0.72, 8.17 ± 0.54 vs 8.68 ± 0.47 mmol/L, P < 0.01), HOMA-IR (8.26 ± 2.50, 7.44 ± 1.23 vs 12.66 ± 1.44, P < 0.01) and serum androgen (0.09 ± 0.03, 0.09 ± 0.03 vs 0.53 ± 0.41 ng/ml, P < 0.01) and the expressions of AMPKα and SIRT11 were increased progressively (P < 0.05). CONCLUSIONS: Both metformin and exenatide can improve the reproductive and endocrine functions of rats with PCOS via the AMPKα-SIRT1 pathway, which may be the molecular mechanism for IR in PCOS and could possibly serve as a therapeutic target.